Stress responses of adolescent male and female rats exposed repeatedly to cat odor stimuli, and long‐term enhancement of adult defensive behaviors. Issue 5 (2nd July 2012) - Wright, Lisa D.; Muir, Katherine E.; Perrot, Tara S.
Abstract In order to characterize the short‐ and long‐term effects of repeated stressor exposure during adolescence, and to compare the effects of using two sources of cat odor as stressor stimuli, male and female adolescent rats (postnatal day (PND) ∼ 38–46) were exposed on five occasions to either a control stimulus, a cloth stimulus containing cat hair/dander, or a section of cat collar previously worn by a cat. Relative to control stimulus exposure, activity was suppressed and defensive behavior enhanced during exposure to either cat odor stimulus (most pervasively in rats exposed to the collar). Only cloth‐exposed rats showed elevated levels of corticosterone (CORT), and only after repeated stressor exposure, but interestingly, rats exposed to the collar stimulus during adolescence continued to show increased behavioral indices of anxiety in adulthood. In this group, the time an individual spent in physical contact with a cagemate during the final adolescent exposure was negatively related to stress‐induced CORT output in adulthood, which suggests that greater use of social support during adolescent stress may facilitate adult behavioral coping, without necessitating increased CORT release. These findings demonstrate that adolescent male and female rats respond defensively to cat odor stimuli across repeated exposures and that exposure to such stressors during adolescence can augment adult anxiety‐like behavior in similar stressful conditions. These findings also suggest a potential role for social behavior during adolescent stressor exposure in mediating long‐term outcomes. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 551–567, 2013